Erdheim-Chester Disease with No Skeletal Bone Involvement and Massive Weight Loss - Salama, Hind; Kojan, Suleiman; Abdulrahman, Shaima; Azzumeea, Fahad; Alhejazi, Ayman (Case Reports in Hematology, 2017)
Erdheim-Chester disease (ECD) is a rare type of non-Langerhans cell histiocytosis, with only 550 cases reported worldwide. ECD is characterized by diffuse histiocytic infiltration of multiorgans. The age of presentation of this disease is typically between 40 and 70 years. Bone disease is the most common symptom, as unique radiological findings of long bone sclerosis occur in 96% of cases. Furthermore, BRAF V600E mutation is detected in 60% of ECD cases. In this manuscript, we are describing a unique case of ECD; the patient is younger than most reported cases and has no bone pain or any skeletal involvement. This patient has unintentionally lost about 50% of his body mass and is suffering from progressive cerebellar manifestations with radiological evidence of cerebellar atrophy, in contrast to the usual ECD manifestation of cerebellar infiltration. In addition, the patient has cardiac, retroperitoneal, and perinephric involvement, but he retains his sexual drive and fertility. A tissue biopsy from the retroperitoneal mass displayed typical morphological and immunohistochemical features of ECD, and BRAF V600E mutation was detected. He was treated with pegylated interferon alpha, but his disease progressed and the treatment was changed to vemurafenib to which he had an excellent response at 6 weeks.